Pengembangan E- Modul Berbasis Model Pembelajaran Flipped Classroom untuk Meningkatkan Hasil Belajar IPA di Kelas IV Sekolah Dasar Gugus 3 Kota Bukittinggi - Mega Darma Yani; Ismira; Annisa Kharisma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low science learning outcomes of elementary school students due to the dominance of conventional teacher-centered methods and the lack of innovative learning media. These conditions cause difficulties in understanding abstract concepts, low motivation, and lack of opportunities for independent learning outside the classroom. This study aims to develop an e-module based on the flipped classroom model to improve science learning outcomes of fourth-grade elementary school students. The method used is Research and Development (R&D) with the 4-D Thiagarajan development model which includes the define, design, develop, and disseminate stages. The research subjects were 24 fourth-grade students of SDN 06 Aur Tajungkang Tengah Sawah Bukittinggi who were selected through total sampling. The research instruments included validation sheets, practicality questionnaires, learning outcome tests, and documentation. Data analysis was carried out through content and construct validity tests, reliability tests, practicality analysis, N-Gain calculations, and independent sample t-tests with SPSS 16.0. The results of the study showed that the developed e-module was highly valid with an average validation value of 96.8% from material experts and 100% from media experts. The practicality test showed a very practical category, with 94.6% from teachers and 91.2% from students, respectively. Effectiveness analysis through N-Gain showed an increase in learning outcomes in the moderate category (0.58), and the t-test confirmed a significant difference between the experimental and control groups (p < 0.05). The flipped classroom-based e-module is valid, practical, and effective, and is recommended to strengthen learning independence and the effectiveness of science learning in the digital era.